2004
DOI: 10.1111/j.1553-2712.2004.tb00687.x
|View full text |Cite
|
Sign up to set email alerts
|

A Multicasualty Event: Out-of-hospital and In-hospital Organizational Aspects

Abstract: During this MCE, the authors observed "rotating" bottleneck phenomena within out-of-hospital and in-hospital systems. For maximal efficiency, hospitals need to fully coordinate the influx and transfer of patients with out-of-hospital rescue services as well as with other hospitals. Each hospital has to immediately deploy its operational center, which will manage and monitor the hospital's resources and facilitate coordination with the relevant institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Media management and public information centres need to be set up. Stress management services should be made available for staff, and regular management debriefings should be held after normality is partially restored (usually within 12–18 hours) 14 , 20 , 28 …”
Section: Disaster Planningmentioning
confidence: 99%
“…Media management and public information centres need to be set up. Stress management services should be made available for staff, and regular management debriefings should be held after normality is partially restored (usually within 12–18 hours) 14 , 20 , 28 …”
Section: Disaster Planningmentioning
confidence: 99%
“…For example, the definition of critical mortality used to assess mass casualty outcomes has been variably defined as the mortality rate among patients presenting with a high ISS (typically Ն15 or 16), completion of nonorthopedic operative management within 24 hours of admission, or admission to an intensive care unit. 18,24,25 "Expectant" patients, referring to those who have such devastating injuries that they are not expected to survive without heroic (and resource-intensive) efforts, are often excluded from calculation of critical mortality in studies of overtriage, even though the proportion of expectant patients may be dictated by the very triage and treatment processes under study (ie, patients with salvageable injuries may become expectant due to delays in operative management). 18 Overtriage itself has been used as a proxy for discussion of trauma and critical care resource allocation during mass casualty events, whereby high overtriage rates have been taken to imply misallocation of scarce resources away from those patients who truly need it.…”
Section: Discussionmentioning
confidence: 99%
“…It was tested by using the road network and hospital location data of Vancouver. A study of a multi-casualty event in Jerusalem, including rescue, emergency medical services deployment and evacuation of casualties, emergency department deployment, staff recall, medical care, imaging procedures, hospitalization, secondary referral, and inter-hospital transfer of patients is provided in [8]. The authors observed bottleneck phenomena and concluded that for maximal efficiency, hospitals need to fully coordinate the influx and transfer of patients, and each hospital has to deploy an operational center.…”
Section: Related Workmentioning
confidence: 99%